Multi-stage decomposition of 5-aminotetrazole derivatives: kinetics and reaction channels for the rate-limiting steps - Yan, Qi-Long; Zeman, Svatopluk; Zhang, Jian-Guo; He, Piao; Musil, Tomáš; Bartošková, Monika (Royal Society of Chemistry, 2014)
The thermal behavior, decomposition kinetics and mechanisms of 1-amino-1-(tetrazol-5-yldiazenyl) guanidine (tetrazene) and 2-(tetrazol-5-yldiazenyl) guanidine (MTX-1) have been investigated using DSC, TG techniques, and quantum chemical calculations. It has been found that MTX-1 is much more stable than tetrazene and MTX-1, and both of them decompose in three steps with different kinetic parameters. Tetrazene is melted-dehydrated at 128.4 °C with a heat absorption of 50 J g−1 and then it starts to decompose at around 118.6 °C with a peak temperature of 126.3 °C covered by a heat release of 1037 J g−1 at a heating rate of 1.0 °C min−1, while MTX-1 starts at 167.7 °C with a main peak of 191.1 °C covered by a heat change of 1829 J g−1 under the same conditions. The activation energy is almost the same for their first decomposition steps (225 kJ mol−1), which are controlled by a three dimensional nucleation and growth model (A3). The mechanisms of the rate-limiting steps are supported by quantum chemical calculations. They could undergo a similar rate-limiting chemical process producing 1H-tetrazole and N2 for both cases, while the former also produces aminocyanamide and the latter produces cyanamide.